Review of the Literature on Current Changes in the Timing of Pubertal Development and the Incomplete Forms of Early Puberty - Farello, Giovanni; Altieri, Carla; Cutini, Maristella; Pozzobon, Gabriella; Verrotti, Alberto (Frontiers in Pediatrics, 2019)
Puberty is a sensitive period of life characterized by the appearance of secondary sex characteristics which leads to a complete sexual maturation. It physiologically starts between the age of 8 and 13 years in girls and 9 and 14 years in boys. In the last two decades, several studies have showed that start of puberty has moved up to younger ages by 12–18 months, and some of the hypotheses trying to explain this change include the role of nutritional status and obesity and the influence of extrinsic factors such as exposure to endocrine-disrupting chemicals (EDCs), as well. The hypothalamic–hypophysis–gonadal axis develops during embryogenesis, and except for a period of activation immediately after birth, remains suppressed until the onset of pubertal development. At the beginning of puberty, the pulse generator is reactivated, probably due to progressive stimulatory influences on GnRH neurons from glial signals and neurotrasmitters. Kisspeptin and its receptor play a fundamental role in this phase. Premature Pubarche/Adrenarche, Premature Thelarche, and Premature Menarche are incomplete forms of precocious pubertal development that have their origin in endocrine mechanisms that only recently have started to be understood. It is important to distinguish these forms from the complete ones in order to reassure patients and parents about the non-evolution of pubertal progression and avoid non-useful treatments with analogous LHRH.